KARAKTER MORFOMETRIK DAN MERISTIK KEPITING BAKAU (Scylla serrata) DI PERAIRAN MANGROVE KAMPUNG SENTOSA BARAT KELURAHAN BELAWAN SICANANG KECAMATAN MEDAN BELAWAN - Delima Sari Siregar; Hasan Sitorus; Ani Suryanti (AQUACOASTMARINE, 2017)
One method for analysis of growth pattern of Mangrove Crab (Scylla serrata) is to measure of morphometric and meristic character in nature. The purpose of this research is to know the morphometric size and the range of Meristik Mangrove Crab and to know the growth pattern of Mangrove Crab in Sentosa mangrove ecosystem. The characters observedwere the width of the carapace, the length of the carapace, the height of the carapace, the optical groove widths, the right and left chela lengths, the length of the right and left profundus chela, the right and left chela, and the fixed meristik character. Morfometric data analysis used cluster analysis to research data by using scale or distance euclidean. The resultof cluster analysis yields the closest resemblance on stage 1 to 8 with the coefficient value of 0,000 (closest) while the furthest resemblance at stage 39 is composed of sample no 1 and 4 with coefficient value 40,535. The equation of regression between the width of carapace and body weight of mangrove crab caught in each station in mangrove waters of Kampung Sentosa Barat is Y = 54,754 + 0,217 X and value R = 0,954 with a negative allometric growth pattern.Keywords: Morphometric, Meristik, Growth Pattern, Mangrove Crab, Sicanang Belawan